Smart card usage for information retrieval / M.A Ismail and M. H. Selamat - Ismail, M.A.; Selamat, M. H. (2002)
The emergence of Electronic Commerce have enhanced the business efficiency, increased responsiveness and accountability and reduced the cost of transaction as it become more common nowadays. Recent developments in encryption, microchips, and computer network technology have enabled consumers to make electronic payments through the usage of a stored-value card or so-called electronic wallet, which money value is stored digitally. The transactions made with stored-value cards resemble transactions made with currency or coin. An information retrieval from digital library can make use of the extraordinary features of smart card to create an efficient, low cost and safe transaction throughout the virtual world. The usage of smart card could settle the hassle of using credit card and the need of central authorization to purchase information of any kind.